Insights into the Renal Pathogenesis in Schimke Immuno-Osseous Dysplasia: A Renal Histological Characterization and Expression Analysis. (January 2015) - Sarin, Sanjay; Javidan, Ashkan; Boivin, Felix; Alexopoulou, Iakovina; Lukic, Dusan; Svajger, Bruno; Chu, Stephanie; Baradaran-Heravi, Alireza; Boerkoel, Cornelius F.; Rosenblum, Norman D.; Bridgewater, Darren
Schimke immuno-osseous dysplasia (SIOD) is a pleiotropic disorder caused by mutations in the SWI/SNF2-related, matrix-associated, actin-dependent regulator of chromatin, subfamily a-like-1 ( SMARCAL1) gene, with multiple clinical features, notably end-stage renal disease. Here we characterize the renal pathology in SIOD patients. Our analysis of SIOD patient renal biopsies demonstrates the tip and collapsing variants of focal segmental glomerulosclerosis (FSGS). Additionally, electron microscopy revealed numerous glomerular abnormalities most notably in the podocyte and Bowman's capsule. To better understand the role of SMARCAL1 in the pathogenesis of FSGS, we defined SMARCAL1 expression in the developing and mature kidney. In the developing fetal kidney, SMARCAL1 is expressed in the ureteric epithelium, stroma, metanephric mesenchyme, and in all stages of the developing nephron, including the maturing glomerulus. In postnatal kidneys, SMARCAL1 expression is localized to epithelial tubules of the nephron, collecting ducts, and glomerulus (podocytes and endothelial cells). Interestingly, not all cells within the same lineage expressed SMARCAL1. In renal biopsies from SIOD patients, TUNEL analysis detected marked increases in DNA fragmentation. Our results highlight the cells that may contribute to the renal pathogenesis in SIOD. Further, we suggest that disruptions in genomic integrity during fetal kidney development contribute to the pathogenesis of FSGS in SIOD patients.